Natural Plant Products: A Less Focused Aspect for the COVID-19 Viral Outbreak - Pandey, Anamika; Khan, Mohd Kamran; Hamurcu, Mehmet; Gezgin, Sait (Frontiers in Plant Science, 2020)
The sudden emergence of COVID-19 caused by a novel coronavirus (nCoV) led the entire world to search for relevant solutions to fight the pandemic. Although continuous trials are being conducted to develop precise vaccines and therapeutic antibodies, a potential remedy is yet to be developed. Plants have largely contributed to the treatment of several human diseases and different phytoconstituents have been previously described to impede the replication of numerous viruses. Despite the previous positive reports of plant-based medications, no successful clinical trials of phyto-anti-COVID drugs could be conducted to date. In this article, we discuss varying perspectives on why phyto-anti-viral drug clinical trials were not successful in the case of COVID-19. The issue has been discussed in light of the usage of plant-based therapeutics in previous coronavirus outbreaks. Through this article, we aim to identify the disadvantages in this research area and suggest some measures to ensure that phytoconstituents can efficiently contribute to future random viral outbreaks. It is emphasized that if used strategically phyto-inhibitors with pre-established clinical data for other diseases can save the time required for long clinical trials. The scientific community should competently tap into phytoconstituents and take their research up to the final stage of clinical trials so that potential phyto-anti-COVID drugs can be developed.